Objetos rituales e identidad - Ventura i Oller, Monserrat (Pontificia Universidad Católica del Perú. Fondo Editorial, 2000)
Shamanism, especially in the indigenous societies of South America, has been characterized by a complex system of material and symbolic inter-ethnic exchange. As part of this system, the objects used in shamanic rituals cannot be interpreted based on the meaning given by each particular culture from which they originate. Rather, they must be analyzed by the meaning that each receiving culture attributes to its supernatural world, which is usually represented by variable and diverse material forms. This theme will be illustrated with the ethnography of the Tsachila indigenous group from Ecuador, which deploys an extensive and complex network of shamanic exchanges.

El chamanismo especialmente en las sociedades indígenas de América del Sur, se ha caracterizado por un complejo sistema de intercambio interétnico material y simbólico. Como parte de este sistema, los objetos utilizados en los rituales chamánicos no pueden ser interpretados a partir del significado que les otorga cada cultura particular de la que son originarios. Sino que deben ser analizados a partir del significado que cada cultura receptora da a su mundo sobrenatural, que es usualmente representado por formas materiales variables y diversas. Este tema será ilustrado con la etnografía del grupo indígena Tsachila del Ecuador, que despliega una extensa y compleja red de intercambios chamánicos.
Ritual objects and identity
Keywords: Antropología; https://purl.org/pe-repo/ocde/ford#5.04.03